THE BASIC ASPECTS OF APPLICATION OF INFORMATIONCOMMUNICATION TECHNOLOGIES IN A SMALL-SCALE BUSINESS AND PRIVATE BUSINESS IN REPUBLIC UZBEKISTAN - Holida N. Ruzmetova (Статистика и экономика, 2016)
Development of a small-scale businessand private business in Uzbekistan inthe conditions of formation of innovative economy is impossible without effective application of the advanced information-communication technologies which givepossibility to develop not only the domestic markets, but also provide an exit onexternal, thereby raising the informationimportance of the country in the international economic market.